ANALYSIS OF THE EFFECTIVENESS OF USING ANDROI BASED "EDUCATIONAL GAME APPLICATIONS" IN IMPROVING MASTERY OF ARABIC VOCABULARY - Putri, Fauziah Abdillah (Proceeding International Seminar of Islamic Studies, 2023)
Games are one of the industries that developed in this era. Games are not only used for entertainment, but also used for educational purposes. The use of android-based educational game applications is one of the alternative media to improve the mastery of Arabic vocabulary. In Arabic language learning, vocabulary is an important element for acquiring skills in communicating. Therefore, the use of android-based educational game applications is a solution so that learning is not boring and  trains focus and makes children interested in continuing to learn. This study aims to analyze the effectiveness of using android-based educational game applications in improving Arabic vocabulary. In this study, researchers used a qualitative approach to the Literature Review method by taking various theories and various kinds of research that had been carried out in previous journals. The results obtained from the data analysis carried out by researchers show that there is an effectiveness in the development of learning in mastering Arabic vocabulary.